Resonating, Rejecting, Reinterpreting: Mapping the Stabilization Discourse in the United Nations Security Council, 2000–14 - David Curran; Paul Holtom (Stability : International Journal of Security and Development, 2015)
This article charts the evolution of the conceptualisation of stabilization in the UN Security Council (UNSC) during the period 2001–2014. UNSC open meetings provide an important dataset for a critical review of stabilization discourse and an opportunity to chart the positions of permanent Members, rotating Members and the UN Secretariat towards this concept. This article is the first to conduct an analysis of this material to map the evolution of stabilization in this critical chamber of the UN. This dataset of official statements will be complemented by a review of open source reporting on UNSC meetings and national stabilization doctrines of the ‘P3’ – France, the UK and the US. These countries have developed national stabilization doctrines predominantly to deal with cross-governmental approaches to counterinsurgency operations conducted during the 2000s. The article therefore presents a genealogy of the concept of stabilization in the UNSC to help understand implications for its future development in this multilateral setting. This article begins by examining efforts by the P3 to ‘upload’ their conceptualisations of stabilization into UN intervention frameworks. Secondly, the article uses a content analysis of UNSC debates during 2000–2014 to explore the extent to which the conceptualisation of stabilization resonated with other Council members, were rejected in specific contexts or in general, or were re-interpreted by member states to suit alternative security agendas and interests. Therefore, the article not only examines the UNSC debates surrounding existing UN ‘stabilization operations’ (MONUSCO, MINUSTAH, MINUSCA, MINUSMA), which could be regarded as evidence that this ‘western’ concept has resonated with other UNSC members and relevant UN agencies, but also documents the appearance of stabilization in other contexts too. The article opens new avenues of research into concepts of stabilization within the UN, and seeks to provide a thorough accounting of the origins, spread, and potential trajectories for the concept and practice of stabilization in UN contexts.